A Philosophy of Gun Violence - Reid, Alan J. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
"In his book A Philosophy of Gun Violence, Alan Reid offers a novel way to rethink our approach to the gun violence epidemic in America. By focusing on the gun as technology, whose design influences the way we use--and abuse--it, he reveals how we may advance gun safety, and calm our violent culture, in a manner that sidesteps the usual pitfalls of the debate." -Firmin Debrabander, Professor of Philosophy, Maryland Institute College of Art, USA "Alan Reid's philosophical meditation on guns anticipates the research from other fields in positing that the mere presence of guns changes human behavior. That fundamental insight is only now finding empirical confirmation, yet it is a testament to Reid's thoughtful, timely, and highly readable analysis that he has arrived at the same conclusion and uses that insight to great effectiveness in this new work." -Robert J. Spitzer, Distinguished Service Professor of Political Science Emeritus, SUNY, Cortland, USA This book uses a philosophy of technology to demonstrate that guns are predisposed for an intentional use, making them inherently non-neutral artifacts. This argument rejects the often-cited value neutral thesis and instrumentalist view that "guns don't kill people; people kill people", and instead, explains the lethality of the gun through the lenses of affordance theory, behavioral design, and choice architecture. Ultimately, this book proposes an ethical and value-sensitive model for gun reform, which embodies the perspective of French philosopher Bruno Latour, who said, "You are different with a gun in your hand; the gun is different with you holding it." Alan J. Reid is an Associate Professor of First-Year Writing & Instructional Technologies at Coastal Carolina University where he teaches courses in composition, new media, and graduate writing and research. He is also an Evaluation Analyst in the Center for Research and Reform in Education at Johns Hopkins University and teaches graduate courses in technology and design for the JHU School of Education.
Ch1: The Gun Problem -- Ch2: A Philosophy Of Technology -- Ch3: Chekhov's Gun -- Ch4: A Violent Nudge -- Ch5: Liberty And Guns -- Ch6: The Future Of The Gun.
Keywords: Technology-Philosophy.; Social sciences-Philosophy.; Crime; Technology; Philosophy of Technology; Social Philosophy; Crime and Technology